ASSESSMENT OF RELATED ANAMNESTIC AND CLINICAL FACTORS ON EFFICACY AND SAFETY OF ANTI-HELICOBACTER PYLORI THERAPY - D. N. Andreev; I. V. Maev; Yu. A. Kucheryavyy; D. T. Dicheva (Архивъ внутренней медицины, 2016)
The article presents the results of a prospective clinical study in which 100 patients with H. pylori-associated peptic ulcer disease of stomach/duodenum were examined. The aim of the study was to assess the effect of concomitant anamnestic and clinical factors on the efficacy and safety of eradication therapy (ET). Type 2 diabetes mellitus is a factor that significantly reduces the efficiency of ET with OR 0.21 (95% CI 0,06-0,69, p = 0,0102). Using a macrolide antibiotics prior to ET during the previous 12 months is associated with a reduction in the effectiveness of H. pylori eradication with OR 0.27 (95% CI 0,08-0,90, p = 0,0342). Despite the lack of statistical significance observed negative effect on the efficiency of ET factors such as smoking and increased BMI. Smoking, female gender, age over 50 years and the presence of type 2 diabetes mellitus had no significant impact on the safety profile of ET.